2010
DOI: 10.1097/meg.0b013e32832fcdf0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with the presence of nonalcoholic fatty liver disease in an adult population in Spain

Abstract: NAFLD prevalence in our population is very high. Male sex, age, metabolic syndrome, insulin resistance and alanine aminotransferase are the factors associated with NAFLD. Furthermore, studies should be carried out with respect to the controversial effect of alcohol on NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
108
2
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(150 citation statements)
references
References 33 publications
11
108
2
19
Order By: Relevance
“…In our study, the overall prevalence of NAFLD in nondiabetic Korean adults was 28.1 % (25.2 % aft er adjusting for sex), which is comparable to recent results of population-based ultrasonographic studies indicating that one out of every four adults has NAFLD ( 18,20,21,23 ). Recently, NAFLD was proposed to be closely associated with insulin resistance and is known to be expressed earlier than metabolic syndrome ( 7,8 ).…”
Section: Impact Of Nafld On Insulin Resistancesupporting
confidence: 74%
“…In our study, the overall prevalence of NAFLD in nondiabetic Korean adults was 28.1 % (25.2 % aft er adjusting for sex), which is comparable to recent results of population-based ultrasonographic studies indicating that one out of every four adults has NAFLD ( 18,20,21,23 ). Recently, NAFLD was proposed to be closely associated with insulin resistance and is known to be expressed earlier than metabolic syndrome ( 7,8 ).…”
Section: Impact Of Nafld On Insulin Resistancesupporting
confidence: 74%
“…Singh et al,(2010)in their comparative study between NASH and ASH clearly showed SGPT levels were more elevated in NASH as compared to ASH(mean being110.82IU/L in NASH and 79.69IU/L in case of ASH).Also showed a higher AST/ALT ratio in ASH as compared to NASH(mean of 1.24+0.81 in ASH and 0.68+0.33 in NASH)This study strongly supports our finding that SGPT is a more relevant marker than SGOT in NASH patients and AST/ALT ratio Is >1 in ASH rather than NASH, which indeed helps in distinguishing between ASH and NASH. This was also reported by Sorbi et al (1999) (18) (20) , Clarket al(2002) (21) , Ong et al (2005) (22) in their studies established the association of severe obesity leading to severe NAFLD. When a Comparison was made between biochemical and radiological grade of fatty liver we found out that as the grade increases there was an increase in all the biochemical parameters (TG and SGPT).…”
Section: Discussionsupporting
confidence: 61%
“…Notably, only 54% of NAFLD cases occurred in patients with elevated serum alanine aminotransferase (ALT) levels, but the vast majority of these individuals had many features of the metabolic syndrome. Epidemiological data from Spain describe similar rates, with a NAFLD prevalence of 25.8% in the adult population 30 . Only a few studies are available from eastern Europe.…”
Section: Nafld In Europementioning
confidence: 68%